Effectiveness of Test Driven Development and Continuous Integration - A Case Study - Amrit, Chintan; Meijberg, Yoni (IT professional, 2018)
In this article we describe the implementation of hybrid agile practices, namely Test Driven Development (TDD) and Continuous Integration (CI) at a Dutch SME. The quality and productivity outcomes of the case study were compared to a performance baseline set by a reference case, a preceding development project of similar context, size, complexity and team. We observed that on applying TDD and CI, a higher number of defects were discovered compared to the baseline case. The team members at the Dutch SME perceived an increase in the focus on quality and test applications, while considering customer acceptance. As a result of the case study, the Dutch SME now has an infrastructure in place to further evaluate software process improvement (SPI) initiatives.